Bus locator: σύστημα ενημέρωσης για διακίνηση μέσω λεωφορείου - Γεωργίου, Νικολέττα (Τμήμα Επικοινωνίας και Σπουδών Διαδικτύου, Σχολή Επικοινωνίας και Μέσων Ενημέρωσης, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
This thesis entitled “Bus Locator: Information System about bus transportation” was developed by Nikoletta Georgiou, an 8th semester student of the department of Communication and Internet Studies, Cyprus University of Technology, under the supervision of Dr. Lampros Lamprinos and was completed in May 2014. This thesis belongs to the field of Information and Communication Technologies. The research strategy followed in this thesis is quantitative, and the research method is the experiment. The purpose of this paper is the presentation and implementation of an economic, flexible and expandable solution for a system that informs potential users about buses. The system includes setting up the infrastructure that will produce the necessary information, and development of an android application for processing and presenting information to the user. A key advantage of this system is that it offers reliable, flexible and quick information to users, in contrast to the static information provided so far in Cyprus.
Keywords: Bus; Bus locator; Information System; Bus transportation; Λεωφορείο